Structure and modal analysis of the last stage blade in steam turbine under low volume flow conditions. (January 2022) - Xu, Meichao; Cao, Lihua; Song, Linsen
Highlights: Prestressed modal analysis of the blade under different conditions is calculated. Cyclic symmetry analysis is adopted to calculate modal characteristics. The temperature of blade tip increases with the decrease of the steam flow. The maximum equivalent stress increases with the decrease of the steam flow. The natural frequencies of the blade decreases under low volume flow conditions. Abstract: To explore the prestressed modal characteristics of the last stage blade in steam turbine under low volume flow conditions, the fluid–structure interaction (FSI) method of ANSYS mechanical + CFX is adopted to consider the effect of flow field on the strength performance of the rotor blade. The cyclic symmetry analysis is adopted to calculate the strength performance and modal characteristics of the rotor blade. The results show that the flow field of the last stage is composed of backflow vortex, separation vortex and tip clearance vortex under low volume flow conditions. The tip clearance vortex has high circumferential velocity and temperature. The maximum deformation of the rotor blade is on the leading edge of the blade at 80% span, and the maximum equivalent stress is on the suction surface at 90% span. With the decrease of the steam flow, the temperature at the blade tip increases significantly, which increases the maximum deformation and the equivalent stress of the rotor blade. The plastic deformation occurs when the steam flow is reduced to 15% turbine heat acceptance (THA). In addition, the elastic modulus of blade material decreases with the increase of temperature, which leads to the decrease of natural frequencies. From 35 %THA to 5% THA condition, the natural frequencies of the blade decrease by 34-136 Hz. This study provides a theoretical reference for the identification, diagnosis and prediction of the vibration of the last stage blade under low volume flow conditions.